Efficient Differentiation of Mouse Induced Pluripotent Stem Cells into Alveolar Epithelium Type II with a BRD4 Inhibitor. (27th December 2019) - Momozane, Toru; Fukui, Eriko; Funaki, Soichiro; Fujii, Makoto; Kinehara, Yuhei; Ito, Emiko; Miyagawa, Shigeru; Ohno, Yuko; Sawa, Yoshiki; Okumura, Meinoshin; Shintani, Yasushi
Abstract : Regenerative medicine has continued to progress for lung biology and lung diseases. Efforts have focused on a variety of different applications for pluripotent stem cells. Several groups have reported successful methods for inducing differentiation of induced pluripotent stem cells (iPSCs) into the airway epithelium such as alveolar epithelium type II (ATII). However, differentiation efficiency varies among reports and improvements are needed. In the present paper, we propose a novel method for elimination of residual undifferentiated murine iPSCs using JQ1, a potent inhibitor of bromodomain (BRD) and extraterminal domain (BET) family proteins, for efficient differentiation into ATII. First, the murine iPSC line 20D-17 was induced to differentiate into ATII over a period of 26 days (days 0-26) using previously reported embryoid body seeding and stepwise differentiation methods. mRNA expressions of differentiation markers including surfactant protein C ( Sftpc ) were confirmed by real-time reverse transcription-polymerase chain reaction (RT-PCR) results, and 17% of the cells were shown positive for prosurfactant protein C (proSPC) in flow cytometry analysis. Next, those cells were cultured three-dimensionally in Matrigel for an additional 14 days (days 26-40), during which JQ1 was added for 4 days (days 28-32) to remove residual undifferentiated iPSCs. As a result, on day 40, the mRNA expression level of Sftpc in the three-dimensional culture was maintained at the same level as on day 26 and shown to be further increased by the addition of JQ1, with 39% of the cells found to express proSPC, showing that differentiation efficiency could be further increased. Three-dimensional culture with BRD4 inhibition by JQ1 improved the differentiation induction efficiency to ATII by removing residual undifferentiated murine iPSCs during the differentiation induction process.